(3OhGhjf GdTYQGA GdSJI GdLGgdjjfs - (3GdGYde GdTfbQj , jhSa Hf SdjeGf Hf YjSi GdTfJeQj GdCfOdSj, CHh GdMLGL,J (B476 (3g` s ((3eMeO Hf jhSa Hf EHQGgje Hf bMWHI s)
(3ChdgG (B:s
(3bGd (B((3GeQD GdbjS(B) (3baGfHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3ef TYQ YfJQI bhdg(B: (3hcGf aJj GdgjLGA jMej PeGQgG hjVQH YfO GdcQ cd HfGf s
(3GfXQ GdLRA GdChd HQbej (B502s
503 (3COH TQM OhGhjf GdTYQGA GdSJIs
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG hHjf SWhQgG HYV GdTQhM s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs